The Tamales of Guagua and Sasmuan enduring existence of a Kapampangan culinary heritage - Hije, Maria Asuncion M. (College of Home Economics, University of the Philippines Diliman, 2021)
The Tamales have its origins from Meso-America dating from 700B.C. Since the dish was brought to Philippine shores via the Galleon Trades, it has been adapted to the Filipino palate and way of life. In the towns of Guagua and Sasmuan in particular, the tamales have remain ubiquitous up to the present in spite of the cosmopolitan culinary landscape in some parts of Pampanga. Using Pierre Bourdiueu's formulations on the relationships between habitus, field, capital, and practice, this study aimed to examine how the tamales maintained its existence and popularity in the said municipalities. It further aimed to investigate the dynamics within the communities, symbolic meanings, and the transformations that took place for tamales existence to withstand the test of time. Theoretical notions about memory, identity, and history were included as important variables in the framework. A qualitative case study research design was used. The dish's history, symbolic relationships, and development were analyzed vis-a-vis the interaction between social units, belief systems, and everyday practices. Emphasis was given on in-depth insights, meanings, and contexts. Key informant interviews, a focus group discussion, and consumer perception surveys were carried out using a combination of in-person meetings and virtual platforms. Thematic analysis and coding using NVivo qualitative analysis software was used to dissect and give meaning to the data collected. The survey results were analyzed using the Fisher Exact Test. The findings of the study revealed a web of interrelated players in the field of tamales-making across history, generations, areas, social classes, tradition, and transformation. It showed how collective memory can shape the narrative history and worldview of a community. In the end, it elucidated the interrelated roles of family, adaptation, resilience, identity, and perception as cohesive elements in maintaining the enduring existence of the tamales in Guagua and Sasmuan. The findings of this study may provide a more comprehensive understanding of the history and symbolic significance of the tamales in the two locales. Such information may be used to develop a more inclusive environment for the livelihood of the tamales producers of Guagua and Sasmuan. It may also contribute to the scarce literature about the Kapampangan tamales that could prompt more preservation efforts and recognition from the different sectors in the culinary and tourism field.